2020
DOI: 10.1038/s41598-020-58653-9
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 promotes uterine inflammation leading to pathological preterm birth

Abstract: It is widely accepted that enhanced uterine inflammation associated with microbial infection is a main causative factor for preterm birth. However, little is known about the molecular basis by which inflammation is associated with preterm birth. Here, we demonstrate that apoptosis signal-regulating kinase 1 (ASK1), a member of the mitogen-activated protein 3-kinase family, facilitates inflammationinduced preterm birth and that inhibition of ASK1 activity is sufficient to suppress preterm birth. ASK1-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Jiang, et al [65] also demonstrated that DUSP9 acts a suppressor for the development of cardiac hypertrophy through the interaction and dephosphorylation of ASK1 to repress p38 and JNK signaling pathways. By activating the p38 and JNK pathways, ASK1 could facilitate infection-induced uterine inflammation leading to preterm birth [66]. Therefore, we speculate that DUSP9 may bind to and dephosphorylate ASK1 to participate in the inflammatory response and PGE2 production medicated by the p38 and JNK signaling pathways in the process of labor.…”
Section: Discussionmentioning
confidence: 95%
“…Jiang, et al [65] also demonstrated that DUSP9 acts a suppressor for the development of cardiac hypertrophy through the interaction and dephosphorylation of ASK1 to repress p38 and JNK signaling pathways. By activating the p38 and JNK pathways, ASK1 could facilitate infection-induced uterine inflammation leading to preterm birth [66]. Therefore, we speculate that DUSP9 may bind to and dephosphorylate ASK1 to participate in the inflammatory response and PGE2 production medicated by the p38 and JNK signaling pathways in the process of labor.…”
Section: Discussionmentioning
confidence: 95%
“…4 a). Mutations in Map7 have been associated with male sterility [ 37 , 38 ], but Map3k5 homozygote mice have been reported to be fertile [ 39 ], suggesting that the loss of the first exon of Map7 is affecting MAP7 protein function, resulting in the observed infertility in rhme affected males. Male and female homozygotes for the rhme deletion had raised thresholds at high frequencies at 4 weeks old, and the hearing loss progressed with age (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we showed that ASK1 suppresses the inflammatory NOD-RIPK2 pathway and cytokine secretion in brown adipocytes. While ASK1 has been reported as a critical regulator of inflammation 23,34,52 , most of these reports demonstrated that ASK1 promotes the inflammatory response. Our finding is unique in that ASK1 suppresses the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%